Pandemia 2020 y el poder del Estado. Daños, impactos y respuestas a zonas desprotegidas en escenarios devastadores - Canaza-Choque, Franklin Américo (2021)
Within a scenario of strong markers, this study aims briefly analyze the power of the State in a space governed by deliberate impacts COVID-19 pandemic and the irruption of neoliberal models in intermediate development countries in Latin America and the Caribbean. For this, purpose a theoretical-documentary analysis in three nominative stages: collection of information and precision concepts, analysis and interpretation of content and, finally, the introduction of new theoretical-reflective elements. From there, two are the final ideas. The first, is that pandemic has only amplified the impact of premeditated public-global ills, in addition to collapsing the health system and massively disintegrating the general welfare and the levels stability of regional order. Meanwhile, the second refers that before a weakened scenario due to the application of neoliberal policies and of dragging of previous structural fractures, the pandemic has made visible the high precariousness of the State and the limits of its power. The pandemic has made visible the high precariousness of the State and the limits of its power. In conclusion, everything leads the strong need to repair, reactivate and reinforce social policies and public powers. That is, the return of the State.